Please explain this step by step.
Differentiate each function.
Y = X2 + 4X +3 V(t)=t2 – 1 Z= A + BeY
√ (X) 4√(t3) Y10
Answer Y’=3 √ (x) + 2 + 3
2 √(X) 2X√(X)
V(t)’=2t - 3
Z’= -10A + BeY
Following is the text part of the solution. Please see the attached file for complete solution. Equations, diagrams, graphs and special characters will not appear correctly here. Thank You.
Chapter 3.1 Derivatives of Polynomials and Exponential Functions.
General rule ...
Derivative of three different polynomials are obtained. All steps have been shown. Equations are typed using equation editor.